Identification of Gastropods on Seagrass Meadows at Makassar Island Waters, Baubau, South East Sulawesi - Bugis, Nila Nikmatia; Cahyani, Waode Sitti; Sirza, LM. Zunaidin (FAPETKAN UNTAD, 2020)
The purpose of this study was to identify, find out the type, composition, diversity, uniformity of gastropods in seagrass beds in the waters of Makasar Island, Bau-Bau City. The benefits to be achieved are providing information, knowing the conditions, and can be the basis for further research in order to maintain the balance of resources and gastropod ecosystems in the waters of the island of Makassar, Baubau City. This research was conducted in January to March 2020, located in the waters of the island of Makassar, Sukanayo Village, Kokalukuna District, Baubau City, Southeast Sulawesi. The method used is a qualitative method which uses primary and secondary data at 3 (three) stations. Gastropods found in the waters of Makassar are 22 species. The most commonly found species are Nassarium globosus and Conus magus. The highest composition of gastropods is around 25% - 40.91%. Diversity index ranges from 2.62 to 2.82, uniformity index ranges from 0.83 to 0.89, and dominance index from 0.17 to 0.21.Â